1969
DOI: 10.1002/recl.19690880209
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium isotope effect in proton magnetic resonance spectra of 3‐hydroxy‐2‐butanone: (Short communication)

Abstract: As part of a study on the oxidation of 3-hydroxy-2-butanone, "acetoin", it became necessary to know the rate of its enolization in acidic aqueous solution. This rate was estimated by following the proton magnetic resonance spectrum when acetoin was dissolved in 2N DzSOd-DzO; see Table I. Except for the hydroxyl hydrogen, position c is deuterated faster than position a, while position b is deuterated at the lowest rate.In a 100 MHz spectrum of acetoin the coupling constant JH-C-C-H = 7.2 f 0.1 Hz and the shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Another choice could be D 2 O. However, it has previously been shown that acetoin or diacetyl exchanges deuterium with D 2 O . Similarly, due to the hydration/dehydration described above, diacetyl will exchange with D 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Another choice could be D 2 O. However, it has previously been shown that acetoin or diacetyl exchanges deuterium with D 2 O . Similarly, due to the hydration/dehydration described above, diacetyl will exchange with D 2 O.…”
Section: Resultsmentioning
confidence: 99%